Managing Director's Global Policy Agenda to the International Monetary and Financial Committee. (Policy Papers; Policy Paper ;, 2014)
etary and Financial Committee Publication Date: April 5, 2014 Electronic Access:Free Full Text. Use the free Adobe Acrobat Reader to view this PDF file Summary:Global activity is strengthening, but the recovery is uneven and remains too weak for comfort, with geopolitical tensions injecting new concerns. Key challenges include risks from a lasting rise in capital flow volatility for emerging and frontier economies and very low inflation in advanced economies, especially the euro area. Creating a more dynamic, job rich global economy remains our collective goal. For this, policymakers should manage the recovery more actively and reinforce their cooperation to minimize negative spillovers and promote financial stability. The Executive Summary is also available in Arabic , Chinese, French, Japanese, Russian , and Spanish.